INTERMEDIATE BAND PHOTOMETRY OF V PUPPIS - MENDOZA, EUGENIO (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1972)
Some 150 observations were made on V Puppis on the (33, 35, 37, 40, 45, 52, 58, 63)-photometric system. The obtained light curves are of high quality. The observed amplitude of the light variations for the primary minimum depends on the spectral region in
BOL AGRI
Keywords: INTERMEDIATE, BAND, PHOTOMETRY, PUPPIS; ASTRONOMIA Y ASTROFISICA; ASTRONOMIA OPTICA; FOTOMETRIA